2021
DOI: 10.1007/s13197-021-05123-3
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and technological characteristics of wooden breast chicken fillets and their consumer acceptance

Abstract: The wooden breast ( WB ) has caused great damages to meat producing industries, being its etiology still not fully understood. Thus, the objective of this work was to investigate biochemistry and technological characteristics of WB chicken fillets and their consumer acceptance. WB fillets were evaluated in regards to color, pH, approximate chemical composition, water holding capacity, cooking loss, shear force, total and soluble collagen, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…Regarding purchase intention, the highest values were showed N and WBM samples, which differed significantly from the WBS. Geronimo et al (2021) evaluated an online scenario with WB chicken fillets and observed that there was a significant reduction in overall acceptance (40.72%), a result that directly and significantly affected low purchase intent. In the present study, a consumer rejection is also identified when the degree of severity of the myopathy is higher.…”
Section: Acceptability and Purchase Intention Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding purchase intention, the highest values were showed N and WBM samples, which differed significantly from the WBS. Geronimo et al (2021) evaluated an online scenario with WB chicken fillets and observed that there was a significant reduction in overall acceptance (40.72%), a result that directly and significantly affected low purchase intent. In the present study, a consumer rejection is also identified when the degree of severity of the myopathy is higher.…”
Section: Acceptability and Purchase Intention Resultsmentioning
confidence: 99%
“…Xing et al (2020) evaluated the acceptability of raw WB chicken breasts, and as a result, the moderate and severe grades obtained lower scores for visual appearance. However, there are still few studies on hedonic responses to WB chicken breast and the impact of consumers' awareness (Geronimo et al, 2021) on this myopathy is ignored.…”
Section: Introductionmentioning
confidence: 99%
“…Wooden breast (WB), a myopathy that affects the pectoral muscle (Pectoralis major) of chicken, is characterized by diffuse hardened areas, whitish protuberances, vascular degeneration, mononuclear cell infiltration, interstitial inflammation, high levels of collagen, and fat fibrillation (Geronimo et al, 2022;Tasoniero et al, 2017;Sihvo et al, 2014). WB myopathy reduces water holding capacity (WHC) and alters rheological and sensory properties of chicken breast, increasing cooking loss and shear force (Xing et al, 2020;Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…WB myopathy is characterized by a significant increase in fat content and a decrease in protein and ash content [9,10]. Lipids in skeletal muscle mainly include triacylglycerols (TGs) and phospholipids, which have significant effects on meat quality and processing characteristics [11].…”
Section: Introductionmentioning
confidence: 99%